(untitled) (Bangladesh Journal of Nuclear Medicine, 2022)
The Standardized Uptake Value (SUV) is one of the fundamental parameters to determine whether a region may be considered a “tumor” or “malignant” from PET-CT-derived images. When a measured SUV value is around 2.5, it is non-malignant. Again small tumorous areas can also show a maximum SUV of <2.5. The main objective of this study is to develop a computer program based on MATLAB for calculating SUV from PET-CT-derived images. This study also projects the way of calculating SUVs in a facile way. The study was particularly concerned with the 2D PET-CT images which were initially derived from commercial medical image processing software. Unlike the DICOM (Digital Imaging and Communications in Medicine) formatted PET-CT produced image, the study calculated these images in JPG (Joint Photographic Group) format. Each command and instruction of this program produces the selection of a region of interest (ROI) sequentially. The programming code also extracted the recognition of the desired ROI in cancerous cells. In the study, we have loaded 13 different PET-CT image samples in the software as input. These inputs were used to reach the final result by using in-house developed MATLAB code. A correlation (polynomial expression) between the calculated SUV and the acquired SUV value from commercial software had been established in order to reduce the error. It is concluded that the in-house developed MATLAB program can be used for rapid estimation of SUV value within an acceptable error range. Bangladesh J. Nuclear Med. 25(2): 98-104, 2022